2006
DOI: 10.1007/s00244-006-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Three Polyethoxylated Tallowamine Surfactant Formulations to Laboratory and Field Collected Fairy Shrimp, Thamnocephalus platyurus

Abstract: Polyethoxylated tallowamine (POEA) is a non-ionic surfactant used in herbicide formulations to increase the efficacy of active ingredients. POEA promotes penetration of herbicide active ingredients into plant cuticles, and in animal species is known to cause alterations in respiratory surfaces. POEA use has increased recently with the advent of "Roundup-Ready" crops; however, its potential effects on aquatic invertebrates are relatively unknown. The aquatic macroinvertebrate Thamnocephalus platyurus (Crustacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 19 publications
2
61
0
6
Order By: Relevance
“…In previous experiments done with the same three surfactants, SurfonicÒ T-15 appeared to be most toxic (2.14 lg/L) to T. platyurus while SurfonicÒ T-5 was least toxic (5.5 lg/L; Brausch and Smith., 2007). As compared to this study, T. platyurus nauplii are 400 times more sensitive to POEA surfactants than D. magna.…”
Section: Resultsmentioning
confidence: 99%
“…In previous experiments done with the same three surfactants, SurfonicÒ T-15 appeared to be most toxic (2.14 lg/L) to T. platyurus while SurfonicÒ T-5 was least toxic (5.5 lg/L; Brausch and Smith., 2007). As compared to this study, T. platyurus nauplii are 400 times more sensitive to POEA surfactants than D. magna.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high solubility in water and extensive use in the environment, the harmful effects of glyphosate on aquatic organisms are of great concern (Cavas and Könen 2007). However, several studies have indicated that the toxic effect of glyphosate is not only in its active principle, but mainly in polyoxyethylene amine surfactant (POEA), which is present in its most common commercial formulation, Roundup (Mann and Bidwell 1999, Perkins et al 2000, Howe et al 2004, Cox and Surgan 2006, Brausch and Smith 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Entre estos adyuvantes, los más comunes son los surfactantes, y en el caso de Roundup® el más ampliamente usado es la polioxietilenamina o tallow amina polietoxilada, un surfactante no iónico con el potencial de afectar adversamente los organismos acuáticos en áreas en las cuales es usado (20).…”
Section: Figuraunclassified
“…Pese a esta información, la preocupación sobre los efectos adversos potenciales de los herbicidas basados en glifosato persiste ya que un número de estudios recientes in vivo en animales muestran que han causado efectos tóxicos en las diferentes especies que han sido expuestas experimentalmente al glifosato, a las formulaciones comerciales que lo contienen, y a uno de sus principales adyuvantes, el surfactante polioxietilenamina o tallow amina polietoxilada (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
unclassified
See 1 more Smart Citation